Somatic and physical traits affecting spring swimming performance in young swimmers - Geladas, N. D.; Nassis, G. P.; Pavlicevic, S. (International Journal of Sports Medicine, 2005)
The aim of this study was to examine the relationship between anthropometry, physical capacity, and sprint swimming performance in swimmers of both genders aged 12 - 14 years old. Anthropometric characteristics (body height and mass, total upper extremity, hand and foot lengths, chest circumference, certain body breadths, and skinfolds), as well as leg explosiveness (horizontal jump) and arm strength (handgrip strength test) were evaluated in 263 competitive swimmers (178 boys and 85 girls) aged 12 - 14 years. Skeletal age was assessed with the Tanner-Whitehouse method. All variables, except for the ankle and shoulder flexibility as well as the skeletal age, correlated with 100 m freestyle performance in boys (r = - 0.46 to - 0.73, p < 0.01). Using a split-sample approach, upper extremity length, horizontal jump, and grip strength were detected as significant predictors of 100 m freestyle performance in boys (R2 = 0.59, p < 0.01). In girls, body height, upper extremity and hand length, shoulder flexibility, and horizontal jump were all significantly related to 100 m freestyle time (r = - 0.22 to - 0.31, p < 0.05) but the degree of association was markedly lower than in boys. In addition, only 17 % of the variance in performance was explained by a combination of body height, hand length, and horizontal jump in girls. These results suggest that 100 m freestyle performance can be partially explained by anthropometry and physical capacity tests in young swimmers. The contribution of these factors to sprint swimming performance is different in boys and girls and this requires further research. These findings could be used for male young swimmers' selection.